PENEGAKAN HUKUM TERHADAP ANAK YANG TIDAK MENGGUNAKAN HELM DI WILAYAH KOTA PEKANBARU - Sundari, Nur Shinta; R, Mukhlis; Elmayanti, Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Law Number 22 of 2009 concerning Road Traffic and Transport states inArticle 291 paragraph (1) every person who drives a motorcycle without wearingan Indonesian national standard helmet as referred to in Article 106 paragraph(8) shall be punished with a maximum imprisonment of 1 (one) month or amaximum fine of Rp.250 (2) every person driving a motorcycle who allows hispassenger not to wear a helmet as referred to in Article 106 paragraph (8) shallbe punished with a maximum imprisonment of 1 (one) month or a maximum fineof Rp.250.000,00 (two hundred and fifty thousand rupiah). However, in realitythere are still many motorbike riders who commit violations by not wearinghelmet when riding, whice can threaten safety if an accident accurs.This type of research can be classified as sociological research becausethe author directly conducts research at the location or field where it isresearched in order to provide a complete and clear picture of the problem understudy. This research was conducted at the Pekanbaru City Resort Police, wherethe population and sample were all parties related to the problem under study.The The results of this study explain that law enforcement is carried out bythe police by conducting operations in one place (stationary) and operationscarried out in motion (hunting) by carrying out preventive and repressiveenforcement. The efforts made by the police are to provide socialization to thecommunity and students. The obstacles faced by the police are the lack of publiclegal awareness and the lack of firmness and discipline of police officers inenforcing the law. It is suggested that law enforcers cooperate more withorganizations, community leaders, and schools in conducting socialization. It issuggested that law enforcers be more assertive and disciplined in enforcing thelaw against violators who do not wear helmets. It is hoped that the people ofPekanbaru City will be more concerned with safety when driving in order tominimize the impact of accidents that occur to children.Keywords: Law Enforcement, Traffic Violations, Children.